Effect of financial constraints on the growth of family and nonfamily firms in Turkey - Bahadır Ergün; Ömer Tuğsal Doruk (Financial Innovation, 2020)
This study examined whether family-owned firms have advantages for accessing external financial sources for growth. Especially in developing countries with imperfect markets, firms can face difficulties accessing external financing sources; however, family-owned firms might have some advantages in this regard over nonfamily firms. Unlike previous studies, this study considered that, in the Turkish context, nonfamily firms are financially constrained while family firms are not. To examine this hypothesis, we used the generalized method of moments (GMM) approach to analyze panel data from 2006 to 2017. The findings showed that financing constraints were a significant obstacle to growth for nonfamily-owned manufacturing firms while the effect was not present for family firms since they are controlled by large, well-established family groups. These results elucidate the relationship between corporate ownership and growth among Turkish firms, especially those with strong links to large family-owned corporations. The results also revealed that reputation and network may facilitate easier access to external financing sources, especially when considering the 'Big Six' family ties of firms.
Keywords: D22; G32; O16; 650; Financing constraints; Firm growth; Turkish manufacturing sector; GMM